Pengenalan dan Pemanfaatan Limbah Kaca Menjadi Produk Bernilai - Rahmawati Cut; Amri Amin; Putri Dini Meutia; Meliyana Meliyana; Muhammad Zardi; Ichsan Syahputra; Tety Sriana; Lusi Dwi Putri; Muhammad Khalis (Universitas Lancang Kuning, 2022)
Glass waste is harmful if it is disposed of and mixed with other waste. A special disposal site is needed to avoid injuring the hands and feet of the garbage collectors, especially at the Final Disposal Site (TPA). Glass waste highly consists of silica (SiO2), which is needed in cement. Glass waste is crushed by a mechanical method using a crusher, creating glass powder with an average size of 54 µm. Cement is mixed with glass powder in a ratio of 4:1. Water cement factor (FAS) is used at 0.3. The partners in this community service activity are primary school-age children in Ateuk Lam Ura Village, Simpang Tiga District, and Aceh Besar District. The success of the resulting product is indicated by its compressive strength, the hardening of cement and glass powder, and the product's visual appearance without any visible pores. The product has good strength and looks neat with a solid surface. The compressive strength of the product obtained is 3.21. Partners are interested and can apply glass waste to flower pots properly.